2011
DOI: 10.1063/1.3632056
|View full text |Cite
|
Sign up to set email alerts
|

Probing the aromaticity of the [(HtAc)3(μ2-H)6], [(HtTh)3(μ2-H)6],+, and [(HtPa)3(μ2-H)6] clusters

Abstract: In this study we report about the aromaticity of the prototypical [(H(t)Ac)(3)(μ(2)-H)(6)], [(H(t)Th)(3)(μ(2)-H)(6)](+), and [(H(t)Pa)(3)(μ(2)-H)(6)] clusters via two magnetic criteria: nucleus-independent chemical shifts (NICS) and the magnetically induced current density. All-electron density functional theory calculations were carried out using the two-component zeroth-order regular approach and the four-component Dirac-Coulomb Hamiltonian, including scalar and spin-orbit relativistic effects. Four-componen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 78 publications
0
8
0
Order By: Relevance
“…The obtained NICS results are opposite to the ones obtained with the ef, BRE, MCI, and HOMA indices. It should be noted that the NICS index, although one of the most popular aromaticity indicators, has been much criticized. There is a notion that NICS quantifies the induced ring currents, although there are a number of examples in which the NICS results and ring current maps do not agree. , It has been shown that NICS does not reflect only the aromaticity of the ring considered because NICS computed in the center of the ring is influenced by delocalization in all cycles involving the given ring. In addition, it has been found that the aromaticity indices based on magnetic response properties are not necessarily correlated with those based on ground-state properties. , To shed more light on the differences found between NICS and other aromaticity indices, we examined the current density maps. Total current density maps of 1 , N- a 1 - 1 , N -l 1 - 1 , N- a 1 a 2 - 1 , and N -l 1 l 2 - 1 are presented in Figure .…”
Section: Resultsmentioning
confidence: 99%
“…The obtained NICS results are opposite to the ones obtained with the ef, BRE, MCI, and HOMA indices. It should be noted that the NICS index, although one of the most popular aromaticity indicators, has been much criticized. There is a notion that NICS quantifies the induced ring currents, although there are a number of examples in which the NICS results and ring current maps do not agree. , It has been shown that NICS does not reflect only the aromaticity of the ring considered because NICS computed in the center of the ring is influenced by delocalization in all cycles involving the given ring. In addition, it has been found that the aromaticity indices based on magnetic response properties are not necessarily correlated with those based on ground-state properties. , To shed more light on the differences found between NICS and other aromaticity indices, we examined the current density maps. Total current density maps of 1 , N- a 1 - 1 , N -l 1 - 1 , N- a 1 a 2 - 1 , and N -l 1 l 2 - 1 are presented in Figure .…”
Section: Resultsmentioning
confidence: 99%
“…For this purpose, an integration plane perpendicular to the molecular plane is chosen in such a way that it extends from the center of the aromatic ring and cuts a specific CC bond. The integration plane can cut any bond in the ring, in whichever part of the bond (not necessarily in its middle point) because the conservation of current (Kirchhoff's current law) ensures that the same value is obtained . However, it is also important that the plane remains away from atomic centers, because atomic centers correspond to singularities, as they have their own current density, which would make integration numerically unstable in their vicinity.…”
Section: Methodsmentioning
confidence: 99%
“…[10][11][12] These contradictions show that chemical bonding and aromaticity of the Re 3 (µ-Cl) 3 Cl 6 are much more complex issues than they initially appeared, and that a more thorough study is needed to sort out these inconsistencies.…”
mentioning
confidence: 86%
“…On the other hand, the NICS value indicates that this cluster sustains a net diatropic ring current, supporting its aromatic character and contradicting the proposal of localized bonds. This picture becomes more confusing if we consider that NICS, due to important contributions from strong local electronic currents, erroneously classified certain transition-metal clusters as aromatic. These contradictions show that chemical bonding and aromaticity of the Re 3 (μ-Cl) 3 Cl 6 are much more complex issues than they initially appeared and that a more thorough study is needed to sort out these inconsistencies.…”
mentioning
confidence: 99%